Impact of COVID-19 Curfew on Eating Habits, Eating Frequency, and Weight According to Food Security Status in Saudi Arabia: A Retrospective Study - Mumena, Walaa (Progress in Nutrition, 2021)
Background/Aim: Nutritional and lifestyle changes resulting from the implementation of the coronavirus disease (COVID-19) curfew could have detrimental effects on individuals’ nutritional health. This study aimed to investigate the impact of COVID-19 curfew on eating habits, food intake, and weight according to food security status in Saudi Arabia.Material and Methods: This retrospective study included 879 participants who were recruited via an online questionnaire. Data on demographics, food security status (via the Food Insecurity Experience Scale), and changes in eating habits, food intake, and weight before and during the curfew were collected.Results: Changes in eating habits (mealtime and daily number of meals) during the curfew were more common among severely food-insecure participants. Having more time to cook was the reason for changes in eating habits in food-secure and mild food-insecure participants, while anxiety caused changes in eating habits in all food-insecure groups. Food unavailability was frequntly reported among severely food-insecure participants. Food insecurity did not affect food intake during the curfew. However, intakes of fruits, savory snacks, and sweets and candies were higher among food-secure participants (p=0.000 for all). Weight increased significantly during the curfew in the food-secure and mildly food-insecure groups (0.98 kg, p=0.004, and 0.56 kg, p=0.014, respectively).Conclusions: Intake of food between meals increased among food-secure participants during the COVID-19 curfew. Health organizations should emphasize via social media the importance of avoiding overconsumption of foods, promoting positive eating habits, and increasing physical activity during the curfew to maintain health and prevent weight gain.